Behavioural interviewing - Leigh, Richard; Garner, Simon; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2005)
This program explores a relatively new method of job interviewing. Interviews are based on previous experiences of the applicant, combined with scenarios and examples to help predict future behaviour
Title from title screen
Executive producer, Mark McAuliffe ; editor, Paul Sutherland ; sound, Wayne Martin ; camera, Walter Repich, Richard Leigh
Voice over: Ben Harding
Keywords: Interviewing; Personnel management